Entre conceber e construir experiência da arte site Specific em Inhotim - Azevêdo, Natállia da Silva (2018)
Tensed the boundaries between art and contemporary architecture from the exploration of the environment as the work itself is the starting point of this dissertation that analyzes cases in the Inhotim Institute in which environments, places to be visited or even buildings altogether are results of collaborative design between artists and architects.